A method for estimating fetal weight based on body composition. (2nd October 2019) - Bo, Chen; Jie, Yu; E, GaoXiu; Chuan, FanGui; Long, ZhangWen
Abstract: Fetal weight is an important factor to determine the delivery mode of pregnant women. The change of fetal weight is significant, according to regular health monitoring of pregnant women. Conventional methods of fetal weight estimation, namely those based on B-ultrasound, are very complicated and the costs are high. In this paper, we propose a new method based on body composition. An abdominal four-segment impedance model is first established upon pregnant women, as well as the method of calculation. A body composition based method is then given to estimate the fetal weight, with the solution given explicitly. Analyses of clinical data reveal the smallness of the error between the estimated value and the actual value. The error between B-ultrasound and the present method is less than 15%.